Is there an association between crown discoloration and pulp necrosis in traumatized permanent teeth? A meta-analysis - Bárbara Suelen MOCCELINI; Nashalie Andrade de ALENCAR; Marcela Baraúna MAGNO; Michele BOLAN; Lucianne Cople MAIA; Mariane CARDOSO (Sociedade Brasileira de Pesquisa Odontológica, 2020)
Abstract The present study aimed to identify the scientific evidence regarding the association between crown discoloration and pulp necrosis in traumatized permanent teeth. A systematic literature search was conducted in the PubMed/Medline, Lilacs/BBO, Scopus, Web of Science, Cochrane Library databases, and grey literature. Quality assessment and bias control were carried out according to the Fowkes and Fulton guidelines. Meta-analysis was performed, and the odds ratio was calculated with a 95% confidence interval. The quality assessment of the evidence was determined for the meta-analysis outcomes using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach. From 2,702 studies identified, five articles met the inclusion criteria. One among these showed no methodological soundness and was excluded from the meta-analysis, and the remaining four studies were included in the meta-analysis. The total number of traumatized permanent teeth evaluated in the meta-analysis was 367. The results showed a positive association between crown discoloration and pulp necrosis in permanent teeth. Teeth with crown discoloration showed 23 times more chance to present pulp necrosis than teeth without crown discoloration (OR 23.82 [1.25, 452.87]; p = 0.03), with a very low certainty of evidence. There is a significant association between crown discoloration and pulp necrosis of traumatized permanent teeth. Due to the very low strength of evidence according to GRADE, this result should be viewed with caution.